A Psychoanalytical Study of Victorian Female Characters in Wilkie Collins’s Neo-Gothic Novel The Woman in White - Soumani, Bassma; Bentahar, Soumia (University of Ammar Theledji -Laghouat, 2020)
This dissertation is an attempt to provide an insight into the status of woman in nineteenthcentury England. It investigates an important subject which is gender inequality in Victorian society. It reveals that woman’s lives at the epoch were deteriorated. Many of their rights including education, work, marriage and inheritance, were neglected. Additionally, the misery of the Victorian women was depicted widely in literature mainly in Neo-Gothic genre. This literary genre combines realistic events with gothic elements. It challenged the depiction of woman as “Angel in the House” through giving interact representations to woman suitable to their real state. It also emphasizes on the psychology of characters. Moreover, the psychoanalytical study of Victorian female’s character will be on Neo-Gothic novel “The Woman in White” written by Willkie Collins in 1859. The analysis is accompanied with Sigmund’s Freud theory of the Uncanny.